Visible and Near-Infrared Emission from Lanthanoid ß-Triketonate Assemblies Incorporating Cesium Cations - Galán, L.; Reid, B.; Stagni, S.; Sobolev, A.; Skelton, B.; Cocchi, M.; Malicka, J.; Zysman-Colman, E.; Moore, E.; Ogden, Mark; Massi, Massimiliano (American Chemical Society, 2017)
The reaction of the ß-triketonate ligands tris(4-methylbenzoyl)methanide and tribenzoylmethanide with the trivalent lanthanoids Eu 3+ , Er 3+ , and Yb 3+ in the presence of Cs + afforded polymeric structures where the repeating units are represented by bimetallic tetranuclear assemblies of formulation {[Ln(Cs)(ß-triketonate) 4 ] 2 } n . The only exception is the structure formed by the reaction of tris(4-methylbenzoyl)methanide, Yb 3+ , and Cs + , which yielded a polymeric assembly where the repeating units are mononuclear Yb 3+ complexes bridged by Cs + cations. Photophysical measurements on the obtained materials confirmed efficient sensitization from the ligand excited states to the 4f* excited states of the three lanthanoids. According to transient absorption data, Er 3+ and Yb 3+ are sensitized via energy transfer from the triplet state of the ß-triketonate ligands. On the other hand, energy transfer to Eu 3+ seems to occur via an alternative pathway, possibly directly via the singlet state or through ligand to metal charge transfer states. The emission measurements confirm efficient sensitization for all three lanthanoids and bright near-infrared emission for Er 3+ and Yb 3+ , a characteristic that seems to be linked to the specific chemical structure of the ß-triketonate ligands.